Protective effects of melatonin against oxidative stress induced by metabolic disorders in the male reproductive system: a systematic review and meta-analysis of rodent models - Dehdari Ebrahimi, Niloofar; Sadeghi, Alireza; Ala, Moein; Ebrahimi, Fatemeh; Pakbaz, Sara; Azarpira, Negar (Frontiers in Endocrinology, 2023)
Background Male infertility is a multifaceted issue that has gained scientific interest due to its increasing rate. Studies have demonstrated that oxidative stress is involved in male infertility development. Furthermore, metabolic disorders, including obesity, diabetes, hypo- and hyperthyroidism, are risk factors for male infertility, and oxidative stress is believed to contribute to this association. Melatonin, functioning as an oxidative scavenger, may represent a promising therapeutic approach for the prevention and treatment of metabolic disorder-associated male infertility. Material and methods We systematically searched three online databases (PubMed, Scopus, and Web of Science) for studies that evaluated the effects of melatonin therapy on metabolic disorders-induce infertility in male rodents. The favorable outcomes were histopathological parameters of testicular tissue, reproductive hormones, and markers of oxidative stress. Then, meta-analyses were done for each outcome. The results are reported as standardized mean difference (Cohen’s d) and 95% confidence interval. Results 24 studies with 31 outcomes were included. Rats and mice were the subjects. Studies have employed obesity, diabetes, hypothyroidism, hyperthyroidism, hyperlipidemia, and food deprivation as metabolic disorders. To induce these disorders, a high-fat diet, high‐fructose diet, leptin, streptozotocin, alloxan, carbimazole, and levothyroxine were used. The outcomes included histopathologic characteristics (abnormal sperm morphology, apoptotic cells, apoptotic index, Johnsen’s testicular biopsy score, seminiferous epithelial height, tubular basement membrane thickness, tubular diameter, sperm count, and motility), weight-related measurements (absolute epididymis, testis, and body weight, body weight gain, epididymal adipose tissue weight, and relative testis to body weight), hormonal characteristics (androgen receptor expression, serum FSH, LH, and testosterone level), markers of oxidative stress (tissue and serum GPx and MDA activity, tissue CAT, GSH, and SOD activity), and exploratory outcomes (serum HDL, LDL, total cholesterol, triglyceride, and blood glucose level). The overall pooled effect sizes were statistically significant for all histopathological characteristics and some markers of oxidative stress. Conclusions Melatonin can reduce damage to male rodents’ gonadal tissue and improve sperm count, motility, and morphology in metabolic diseases. Future clinical studies and randomized controlled trials are needed to evaluate the safety and effectiveness of melatonin for male infertility in patients with metabolic diseases.